NURSING CARE FOR POST-CAESAREAN WOUND DEHISCENCE AND URINARY RETENTION ON POD 19 - Aini, Astri Mufti; Widiasih, Restuning (Journal of Maternity Care and Reproductive Health, 2025)
The postoperative period following a cesarean section (CS) is a critical phase of physical and psychological recovery and carries the risk of complications such as wound dehiscence and urinary retention. If not properly managed, these complications may lead to prolonged pain, extended treatment duration, increased risk of infection, and long-term bladder dysfunction. This case report aims to identify the contributing factors to post-CS complications and describe nursing interventions that may prevent further deterioration. A descriptive observational design with a nursing care approach was used, conducted from 17-23 October 2024. The subject was a post CS POD 19 mother with a history of IUFD with complications of wound dehiscence and urine retention. Assessment findings revealed inadequate nutritional intake, insufficient early mobilization, and poor medication adherence, all of which contributed to the complications. Additionally, the use of honey as a natural antimicrobial showed potential benefits in supporting wound healing. These findings highlight that improper management may prolong treatment and increase the likelihood of additional complications. Therefore, comprehensive nursing care, continuous monitoring, and effective patient education are essential to improve adherence and support optimal recovery.Keywords: Cesarean section, postoperative complications, postpartum women, urinary retention, wound dehiscence.